(untitled) (Bangladesh Journal of Medical Science, 2014)
Background: Families dealing with mentally retarded children undergo stress. Sociodemographic factors play a role in stress and coping mechanisms. This paper highlighting on stress and its relation with demographic variables of families with mentally retarded children is a part of a broader study on stress and coping in families with mentally retarded children. Objectives: 1. Study the sociodemographic profile of families with mentally retarded children. 2. Study the association of stress with sociodemographic variables. Material and methods: A cross sectional study was done on hundred families of mentally retarded children enrolled in special schools at Indore. Sampling procedure was convenience sampling. The study tool was a validated, pretested instrument called as the Family interview for stress and coping in mental retardation, (FISC-MR). Results: Families were found to be suffering from stress. The stress ranged from mild to severe, however it was not significantly associated with the sociodemographic variables except with maternal education level. Conclusion: Families of mentally retarded children undergo stress. Socio-demographic factors play a role in the development of stress in families with mentally retarded children. DOI: http://dx.doi.org/10.3329/bjms.v13i4.20551 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.378-382